IMPLIKASI NORMATIF DAN SOSIOLOGIS DICABUTNYA KEPPRES NO. 3 TAHUN 1997 TERHADAP PERDA NO. 27 TAHUN 2011 SEBAGAI PAYUNG HUKUM PENGENDALIAN PEREDARAN MINUMAN BERALKOHOL DI BANJARMASIN - Nurul Listiyani (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2015)
Legal issues raised in this study is the local government authority in the making of regulation and relationship Decree No.3 of 1997 as the release of Bylaw No. umbrella law. 27 in 2011. With normative research methods, it can be analyzed that the discharge regulation as one local government authority must not conflict with the rules that are in it. If there is a conflict then a decision will be annulled / evaluated its existence by the Supreme Court. The analysis is interesting because it turns out 3 of Presidential Decree 1997 and then withdrawn so that the settings Alcoholic drinks no longer have legal protection. Kata kunci : minuman keras, otonomi daerah, peraturan daerah, payung hukum, dampak